Politeness Strategy of Direct Speech Acts in the Poto Wua Ta'a Ceremony - Balik, Lusiana Mariyeta; Alinda, Marta (Pioneer: Journal of Language and Literature, 2022)
Politeness is very important in society as a social control during social interaction. This study aimed at analyzing the types of politeness strategy of direct speech act in the poto wua ta'a ceremony. The method used in this study was descriptive qualitative method, in which the researcher used politeness theory by Brown and Levinson (1987) to analyze, interpret and discuss the data in a form of utterances in poto wua ta'a ceremony. The result of the study showed that the politeness strategy used were negative politeness strategy, positive politeness strategy and off record strategy. However, the dominant strategy used in the ceremony of the poto wua ta'a was negative politeness strategy such as be conventionally indirect, be pessimistic, state the face threatening acts (FTA) as a general rule, as well as minimize the imposition. Thus, the use of negative politeness strategy made the hearer to be more respected and would do something willingly without pressure from the speaker.